A Movable Fog-Haze Boundary Layer Conceptual Model Over Jianghuai Area, China - Liu, Duanyang; Yan, Wenlian; Qian, Junlong; Liu, Mei; Wang, Zida; Cheng, Muning; Peng, Huaqing (Frontiers in Environmental Science, 2021)
The Jianghuai area is an “important” region not only for its local pollutant accumulation but the belt for pollutant transportation between North China and the Yangtze River Delta during the winter half of the year (often from October to next February). In this study, a movable boundary layer conceptual model for the Jianghuai area in the winter half of the year is established based on the analyses of characteristics of atmospheric circulations and boundary layer dynamic conditions. This conceptual model can well explain the causes of air quality change and frequent fog-haze episodes. Variations of the intensity and range of the cold and warm fronts in the Jianghuai area in the winter half of the year lead to form a movable boundary in this area. When the southerly wind is strong, or affected by strong cold air mass, the air quality in the Jianghuai area may be excellent with a low air pollution index; Two atmospheric circulations provide favorable conditions for the fog-haze formation and maintenance in Jianghuai area: 1) When the shallow weak cold air mass is below the deep moist warm air mass, a stable temperature inversion occurs. The pollutants are transported to the Jianghuai area by the weak cold air mass, and local emissions also accumulate. As a result, a severe air pollution episode appears. 2) When the northerly cold air mass is as intense as the southerly moist warm air mass, the pollutants transported from North China as well as local emissions will continuously accumulate in the study area, which may lead to more severe air pollution. This conceptual model can help us analyze atmospheric diffusion capacity, and benefit the forecast and early warning of airflow stagnation area and fog-haze episode.